Application of Box-Behnken Design for the Extraction of Padina australis - Muhammad Nursid; Anissa Permatasari; Utami Dyah Syafitri; Irmanida Batubara (Molekul, 2022)
Optimization extraction of the brown algae Padina australis using the Box-Behnken design has been carried out. Box-Behnken design in relation to Response Surface Methodology analysis was conducted with four experimental factors (i.e., solvent concentration, temperature, extraction time, and sample to solvents ratio) towards the responses of yield antioxidant, anti-tyrosinase, anti-glycation, total phenolic content, and fucoxanthin content, completing with 29 running experiments. P. australis extraction's optimum condition was acquired at 79.99% solvent concentration, 18.48 hours extraction time, 44.50ºC temperature, and 1:9 ratio powders and solvents. The optimum condition provided a 7.30% extraction yield, 43.94% antioxidant activity, 86.83% anti-tyrosinase, 98.06% anti-glycation, 9.53 mg GAE/g total phenolic content, and 347.55 µg/g fucoxanthin content. Respond Surface Methodology analysis with the Box-Behnken design succeeded in making the appropriate model for producing the optimum P. australis extract.